EFEKTIFITAS GEL EKSTRAK DAUN BINAHONG TERHADAP JUMLAH MAKROFAG PADA PENYEMBUHAN LUKA INSISI MENCIT YANG DIINDUKSI ALOKSAN - Putu Sulistiawati Dewi; Setiawan Setiawan (Universitas Baiturrahmah, 2021)
Introduction: diabetes mellitus is a disorder of carbohydrate, fat, and protein metabolism which is characterized by an increase in blood glucose levels (hyperglycemia) due to secretion and insulin, or decreased insulin action. The amount of costs incurred and the difficulty of handling diabetic wounds, it is necessary to find alternative medicines that are cheaper, one of them is herbal plants. One of the herbs is binahong leaf (Anredera cordifolia). Binahong leaves have active compounds alkaloids, saponins, flavonoids, and terpenoids. Objectives: the purpose of this study was to determine the effectiveness of binahong leaf extract gel against decreasing the number of macrophage cells in incision wound healing of alloxan induced mice (Mus musculus). Materials and methods: 24 mice induced with alloxan were then divided into four groups, such as application of binahong leaf extract gel concentration of 25%, 30%, 35% and application of CMC-Na 2% gel as a control group. All treatment given within 4 days. The data obtained were analyzed using One Way Anova and continued with LSD (Least Significant Differences). Result: from the results of this study indicate that the treatment of binahong leaf extract gel concentrations of 25%, 30%, and 35% effectively decreased the number of macrophage cells compared to the control group. Conclusion: this study concluded that binahong leaf extract gel concentration of 35% was more effective on decreasing the number of macrophage cells in incision wound healing of alloxan induced mice.